Study on the Analyzing and Simulating Method of Workspace of Force Reflecting Main Manipulator - Qu Jinxing; Feng Feng (Jixie chuandong)
As a crucial kinematics index for main manipulator performance,the workspace needs to be considered in design,control and application,it represents the main manipulator action range,and the working performance of main manipulator is discussed from the aspects of geometry. The functional relationships between robotic end- effector space position and variables for robotic joints are obtained through the main manipulator forward kinematics solution calculation,a simulation of main manipulator workspace is conducted by adopting numerical,graphical method and analytic method in the Matlab. According to the position information of collecting by 3D electromagnetic tracking system,through the quantitative and qualitative analysis,the correctness of the simulation method for solving the main manipulator workspace is verified. Finally,according to the shape volume of workspace,the location layout of the main manipulator on the operation table is decided,meanwhile,meanwhile,the characteristics and applications of the three kinds of main manipulator workspace solving methods are given,a basis for the kinematics performance index evaluation and preoperation surgical planning is provided.